Usługi biegłego rewidenta dla małych jednostek dotyczące prowadzenia rachunkowości i rewizji finansowej - Misińska, Danuta (Auditor Services for Small Entities Concerning Leading Accounting and Financial Reports, 2007)
The article discusses the necessity of leading accounting and financial reports by small entities. Because in recent years in most of small companies accounting was not leading properly, it was the task of international group of experts, who in 2000 formulated by principles of financial accounting and accountancy of small and medium-sized companies (International Accounting Standard -41).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 131-136